Reviewing the Heat: Exploring Global Warming Patterns in the Southern Hemisphere - Ferrelli, Federico (2024)
This manuscript presents a review of the effects of global warming in the Southern Hemisphere (SH), serving as a tool to summarize the primary impacts. Given the varying degrees of development across the study area, understanding the consequences that each continent is relevant for effective action and raising awareness about the significance of this phenomenon. The results are presented by dividing the study area into South America, Africa, Oceania, and the Southern Ocean. It was observed that each continent experiences diverse effects: in South America, major ecosystems such as the Amazon and Pampas are undergoing continuous degradation, posing a threat to CO2 absorption and food security; in Africa, a progressive warming affecting the entire continent is observed, with harmful impacts on the population due to its high dependence on precipitation for regional economies. In Oceania, the effect of rising sea levels is more pronounced, resulting in climate refugees and the imminent disappearance of countries. Similarly, oceanic ecosystems show degradation, changes in marine currents, and the emergence of increasingly intense meteorological phenomena. Given the analysis, the importance of raising awareness about the need to reduce emissions and educate the entire population becomes evident.